Hepatic sarcoidosis: pathogenesis, clinical context, and treatment options. (1st September 2016) - Syed, Umer; Alkhawam, Hassan; Bakhit, Mena; Companioni, Rafael A. Ching; Walfish, Aron
Abstract: Sarcoidosis is typically characterized as a non-caseating granulomatous disease that has the ability to affect multiple different organ systems. Although extra-thoracic sarcoidosis can occur in the presence and also without lung involvement, isolated extra-pulmonary disease is rare. The liver is the third most commonly affected organ system after the lungs and lymph nodes. When discussing hepatic sarcoidosis it is important to keep in mind that many patients in this population may not present as one would typically expect since most of the patients are asymptomatic or have mild presentations. Therefore, the diagnosis can be difficult at times since no single laboratory or imaging study can definitively diagnose this systemic disease. In the rare case of some patients where there is difficulty in discerning between different pathologies, the use of image-guided tissue biopsy may be necessary to establish a diagnosis. At the current time, there are no clear guidelines for the management of hepatic sarcoidosis and are mostly dependent on a patient's clinical status at time of presentation. The current body of research in regard to treatment suggests steroids to be the mainstay of therapy. However, there is a role for additional immunosuppressive therapy in cases where the initial treatment is refractory to steroids. In this manuscript, we discussed the pathogenesis of liver sarcoidosis and context of its presentation. In addition, the differential diagnosis and imaging evaluation in this population is discussed. Finally, treatment options are reviewed in setting of previous studies for liver sarcoidosis.